Cytotoxicity, Genotoxicity and Disturbance of Cell Cycle in HepG2 Cells Exposed to OTA and BEA: Single and Combined Actions - Ana Juan-García; Josefa Tolosa; Cristina Juan; María-José Ruiz (Toxins, 2019)
Mycotoxins are produced by a number of fungal genera spp., for example, Aspergillus, Penicillium, Alternaria, Fusarium, and Claviceps. Beauvericin (BEA) and Ochratoxin A (OTA) are present in various cereal crops and processed grains. This goal of this study was to determine their combination effect in HepG2 cells, presented for the first time. In this study, the type of interaction among BEA and OTA through an isobologram method, cell cycle disturbance by flow cytometry, and genotoxic potential by in vitro micronucleus (MN) assay following the TG 487 (OECD, 2016) of BEA and OTA individually and combined in HepG2 cells are presented. Cytotoxic concentration ranges studied by the MTT assay over 24, 48, and 72 h were from 0 to 25 µM for BEA and from 0 to 100 µM for OTA, while BEA + OTA combinations were at a 1:10 ratio from 3.4 to 27.5 µM. The toxicity observed for BEA was higher than for OTA at all times assayed; additive and synergistic effects were detected for their mixtures. Cell cycle arrest in the G0/G1 phase was detected for OTA and BEA + OTA treatments in HepG2 cells. Genotoxicity revealed significant effects for BEA, OTA, and in combinations underlining the importance of studying real exposure scenarios of chronic exposure to mycotoxins.